Assessment of Knowledge, Attitude, and Negative Emotions among Gynecologic Oncology Patients during the Coronavirus Disease-19 Pandemic - Harsono, Ali Budi; Erfiandi, Febia; Setia, Tendi Robby; Nisa, Aisyah Shofiatun; Winarno, Gatot Nyarumenteng Adhipurnawan (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Coronavirus disease-19 (COVID-19) has been declared a world pandemic by World Health Organization (WHO). The ability of COVID-19 to be transmitted quickly causes fear and excessive worry in certain groups of people, such as the elderly and those with chronic diseases, including oncology and gynecology patients and the caregivers around them (family members). AIM: This study investigates knowledge, attitude, and negative emotions among gynecologic oncology patients and their families during the COVID-19 pandemic at Hasan Sadikin Public Hospital. METHODS: In this descriptive study, 100 patients with gynecologic malignancies at Hasan Sadikin Hospital, Bandung, Indonesia, were assessed in May 2020–April 2020, who asked for their current knowledge, attitude, as well as negative emotions through Depression Anxiety Stress Scale (DASS-42). RESULTS: The average age of the respondents in this study was 45.50. There were 31 respondents with low-level knowledge, 36 with moderate-level knowledge, and 33 with a high level of knowledge about COVID-19. Based on the attitude assessment, only 44 respondents (44%) always wore masks, 54 (54%) kept a distance of 1 meter, and 42 (42%) kept away from the crowd. An evaluation using the DASS-42 showed that 3, 4, and 0 subjects experienced severe depression, severe anxiety, and severe stress, respectively. CONCLUSIONS: All Indonesian citizens must take necessary measures to prevent COVID-19, including wearing masks, maintaining a minimum distance of 1 m, and washing hands. This study found that not all respondents could comply with the health protocols that were carried out to prevent the transmission of COVID-19. Respondents who experienced severe depression and severe anxiety needed further attention to determine whether they required counseling with a psychiatrist.